Polidocanol versus glucose in the treatment of telangiectasia of the lower limbs (PG3T) Protocol for a randomized, controlled clinical trial - Bertanha, Matheus [UNESP]; De Camargo, Paula Angeleli Bueno [UNESP]; Moura, Regina [UNESP]; Yoshida, Winston Bonetti [UNESP]; Farres Pimenta, Rafael Elias [UNESP]; De Oliveira Mariuba, Jamil Victor [UNESP]; Alcantara, Giovana Piteri [UNESP]; De Paula, Dênia Reis [UNESP]; Sobreira, Marcone Lima [UNESP] (Wolters Kluwer, 2016)
Background: Telangiectasias are defined as small venules abnormally dilated, located in the intradermal portion of the skin, of reddish or bluish tinge, their diameter not exceeding 1mm; they are classified by the American Venous Forum as mild venous disease CEAP C1. Conventional treatment consists of chemical sclerotherapy, considered a minimally invasive technique with rapid clinical recovery. A wide variety of sclerosing solutions can be used for this purpose. Methods/design: This project intends to include 96 patients that will be randomized to a triple-blind study. Inclusion criteria are women between 18 and 65 years, with telangiectasia on the lateral thigh. Male patients, female patients with chronic venous disease CEAP 2 to 6, women with allergies, pregnant, breastfeeding, with any type of skin problems or any decompensated clinical disease will be excluded. All patients included will be submitted to venous ultrasound mapping in order to rule out venous disease not clinically visible, deep venous system insufficiency, and insufficiency of the ostial valve of the great saphenous vein. One group will be treated with glucose 75% solution and the other will receive polidocanol 0.2% diluted in glucose 70%. Each patient will receive only 1 treatment session in 1 single member. The volume of sclerosing solution will not exceed 5mL and the treatment area will be limited to a region of 150cm2 on the lateral thigh. Clinical follow-up will be: 1 initial visit, when the clinical report will be filled; photographic record and treatment with sclerotherapy (D0); follow-up visits after 7 and 60 days (D7 and D60, respectively), always with clinical and photographic documentation. Discussion: The project intends to evaluate the efficacy and safety of sclerotherapy in eliminating telangiectasia in a predetermined area in order to establish efficacy and safety parameters for the treatments presented. Conclusion: This protocol for clinical trial will provide date to determine the efficacy and safety of sclerotherapy with the solutions presented. Trial registration identifier: ClinicalTrial.gov NCT02657252 Date: 01/12/2016 (retrospectively registered).
Keywords: Glucose solution; Hypertonic; Sclerosing solutions; Sclerotherapy; Spider veins; Telangiectasis; Varicose veins; Veins